The Development of BridalGo: An Online Platform for Wedding Couples Using Structured Approach - Yosman, Yusrin; Nur Ariffin Mohd Zin, (Applied Information Technology And Computer Science, 2021)
BridalGo is an online platform for brides and grooms to choose the needs for the wedding they want. The system will serve as a bridal search website, where website visitors can compare bridal price offers and find the best prices quickly and easily. The purpose of developing this system is to solve the problem of the bride in finding the needs for the wedding ceremony such as the throne, dress, make-u and feast suitable for their wedding. Through this system, the bride and groom can make reservations on specific brides. It can simplify the process of recording and storing payment data so that it is easier to know the payment time information and the rest which can facilitate the cancellation process so that customers can know the status of the order. The programming language that will be used to develop this system are hypertext preprocessor which is PHP language, hypertext markup language (HTML) and Cascading Style Sheets (CSS) for user interface design. PhpMyAdmin will be used as database storage and. The system was developed using the iterative model and based on structured approach. Brides can also see their booking activities in the management interface. Users can use the website easily and can do it anywhere and anytime. The development of this system will help brides to make wise decisions about their wedding and bridal shops can have a high chance of improving their marketing.